Kinetika reduksi kalsium oksalat dan pengeringan umbi talas (Colocasia esculenta L.) pada perlakuan perendaman dengan larutan NaCl - Sigit Uji Marzuki; Kristina Desideria Putri Yolanda; Sri Rezeki; Syahrul Khairi (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Calcium oxalate in taro tubers is an anti-nutrient that can cause itching and kidney stones. The challenge in taro processing was reducing the calcium oxalate levels contained therein. In this research, the effect of the NaCl solution's concentration and temperature was studied regarding the reduction of the calcium content of taro tubers in the NaCl solution and its rate of reduction kinetic and drying kinetics. Soaking was carried out in NaCl solution with a concentration of 0, 2, 4, and 6% at room temperature and 40, 50, and 60°C. Soaking with 6% NaCl solution at room temperature can reduce calcium oxalate levels from 1229 mg/100 g to 507 mg/100 g on a dry basis within 120 minutes. Meanwhile, soaking at 60°C with 6% NaCl concentration reduced the calcium oxalate content from 1229 mg/100 g on a dry basis. A kinetic model of calcium oxalate reduction was proposed by considering the diffusion, reaction, and thermal decomposition mechanism of calcium oxalate in NaCl solution. The proposed model has good accuracy with the R2 value for the calcium oxalate reduction rate constant between 0.9278 and 0.9937. At the end of drying, the taro tubers soaked in 0% NaCl solution had the smallest moisture ratio of 0.0014 and an effective diffusivity of 12.99E-09 m2/s. The Page model is the best thin layer drying model to describe the drying of taro tuber slices, with the highest R2 of 0.9999 and the lowest RMSE of 0.0034.